Math, asked by Anonymous, 3 months ago

If the distance between the points (t, t) and (4, 5) is (t - 3) units, then the value of t can be​

Answers

Answered by kumrbirjesh95
8

Answer:

t=8 , 4

hope you understand well mark it brilliant if you understand

Attachments:
Answered by payalchatterje
1

Answer:

Required value of t is 8 or 4.

Step-by-step explanation:

Given, distance between (t, t) and (4, 5) is (t - 3).

For solving this problem we should know what is the distance formula of two points ?

Let,(a,b) and (c,d) be two points.

Therefore distance between them

 \sqrt{ {(a - c)}^{2}  +  {(b - d)}^{2} }

unit .

Here

a = t \\ b = t\\ c = 4 \\ d = 5

So, distance between (t,t) and (4,5) is

 \sqrt{ {(t - 4)}^{2}  +  {(t - 5)}^{2} }

According to question,

 \sqrt{ {(t - 4)}^{2}  +  {(t - 5)}^{2} }  = t - 3

 {(t - 4)}^{2}  +  {(t - 5)}^{2}  =  {(t - 3)}^{2}

{t}^{2}  - 8t + {4}^{2} +  {t}^{2}  - 10t +  {5}^{2}  =  {t}^{2}  - 6t +  {3}^{2}

  {t}^{2}  - 8t +  16  +  {t}^{2}  - 10t +  25  =  {t}^{2}  - 6t +  9

 {t}^{2}  +  {t}^{2}  -  {t}^{2}  - 8t - 10t + 6t = 9 - 16 - 25

 {t}^{2}  - 12t = 32

 {t}^{2}  - 12t - 32 = 0

 {t}^{2}  - (8 + 4)t - 32 = 0 \\  {t}^{2}  - 8t - 4t - 32 = 0 \\ t(t - 8) - 4(t - 8) = 0 \\ (t - 8)(t - 4) = 0

Product of term is zero then they are separately zero.

t - 8 = 0 \\ t = 8

and

t - 4 = 0 \\ t = 4

Here applied formula,

 {(x  -  y)}^{2} =   {x}^{2}  - 2xy +  {y}^{2}

Some important Algebra formulas.

(a + b)² = a² + 2ab + b²

(a − b)² = a² − 2ab − b²

(a + b)³ = a³ + 3a²b + 3ab² + b³

(a - b)³ = a³ - 3a²b + 3ab² - b³

a³ + b³ = (a + b)³ − 3ab(a + b)

a³ - b³ = (a -b)³ + 3ab(a - b)

a² − b² = (a + b)(a − b)

a² + b² = (a + b)² − 2ab

a² + b² = (a − b)² + 2ab

a³ − b³ = (a − b)(a² + ab + b²)

a³ + b³ = (a + b)(a² − ab + b²)

Know more about Algebra,

1) https://brainly.in/question/13024124

2) https://brainly.in/question/1169549

Similar questions